Cultural Diversity Interactive Multimedia to Improve Cultural Literacy and Citizenship of Elementary School Students - Pratiwi Kartika Sari; Cut Mutiara (Yayasan Keluarga Guru Mandiri, 2022)
The problem in research schools is the lack of interest in reading. This research aims to describe the development of interactive multimedia cultural diversity of my nation, know the feasibility of developing interactive multimedia products of my nation's cultural diversity, knowing the effectiveness of interactive multimedia development of my nation's cultural diversity. The method used is RD (Research and Development) with Hannafin Peck models that have needs analysis, design, development, or implementation stages. The study was conducted on grade I-VI elementary school students. Media expert test results score 81.4% with excellent criteria; experts score 96.25% with perfect measures; linguists score 97.5% with ideal standards. Based on the experts' assessment, this medium is very viable. While the effectiveness test conducted with the t-test with pretest-posttest obtained a score of 0.000 sig lower than 0.05, this proves a significant difference between pretest and posttest results to improved cultural literacy and student citizenship with an average score of 96.47%. So it can be said that interactive multimedia includes very effective criteria as a medium of learning and improves cultural literacy and student citizenship.